Ratiometric Quantum Dot–Ligand System Made by Phase Transfer for Visual Detection of Double-Stranded DNA and Single-Nucleotide Polymorphism - Liu, Yuqian; Ye, Mingfu; Ge, Qinyu; Qu, Xiaojun; Guo, Qingsheng; Hu, Xianyun; Sun, Qingjiang (Analytical chemistry (Washington), 2016)
We have developed a proof-of-concept quantum dot–ligand (QD–L) system for visual selective detection of nucleic acids, in combination with a ratiometric fluorescence technique. This system comprises a dual-emission QDs nanohybrid formed by embedding a red-emission QD (rQD) in a silica nanoparticle and electrostatically assembling green-emission QDs (gQDs) onto the silica surface, as the signal displaying unit, and a hydrophobic compound, dipyrido[3,2-a:2′,3′-c]phenazine (dppz), attached onto the gQDs surface via phase transfer, as the ligand as well as fluorescence quencher of gQDs. This system is successfully used for quantification of double-stranded DNA (dsDNA). Because of its avid binding with dppz, dsDNA can break up the QD–L system, displacing the dppz ligand from the gQDs surface and restoring the gQDs emission. Since the red emission of embedded rQDs stays constant, variations of the dual-emission intensity ratios display continuous color changes from orange to bright green, which can be clearly observed by the naked eye. More importantly, this system is advantageous in terms of specificity over a QD ionic conjugate, because the electrical neutrality of dppz excludes its nonspecific electrostatic association with dsDNA. The QD–L system also is capable of detecting single-nucleotide polymorphism, exhibiting sequence-specific ratiometric fluorescence as a QD-bioconjugate does, but possessing the obvious advantage in terms of low cost, with the avoidance of modification, labeling, and purification processes. Therefore, the QD–L system provides an extremely simple but general strategy for detecting nucleic acids in a facile, sensitive, and specific manner.